Analisis Hukum Problematika Jaringan Sutet Sebagai Proyek Strategis Nasional (PSN) Serta Solusi Dari Perspektif Hukum Pancasila - fahmi, wahyu (Journal of Law and Administrative Science, 2023)
Abstract. Residents of the Talaga Bestari housing complex, Cikupa, Tangerang, agreed to reject the construction of the 500 KV SUTET (Extra High Voltage Airline) line that runs through their residential area because it violates regulations, endangers the community, and has never been included in the Tangerang Spatial Development Plan. The development of the Sutet network by a national strategic project is a form of land acquisition, this is contained in Article 1 point 2 of Law no. 2 of 2012 concerning Land Acquisition for Development in the Public Interest which states that land acquisition is an activity of providing land by providing proper and fair compensation to the entitled party. This study uses a research method that is carried out is a type of normative legal research (doctrinal research), namely. library law research. With the aim of providing solutions to development conflicts with development solutions using the Pancasila perspective.